STRATEGI PENINGKATAN KUALITAS PAKAN AYAM PEDAGING BERBENTUK CRUMBLE DENGAN METODE SIX SIGMA DAN HOUSE OF QUALITY - Sylvia; Helena Juliana Kristina; Salomon, Lithrone Laricha (Jurnal Mitra Teknik Industri, 2023)
The company is required to provide the best quality with zero defects in the products they produce. However, zero defects cannot be realized. Therefore, strategies were developed to improve product quality using the six sigma method (DMAIC) and the house of quality. The object of research in this study was crumble-shaped broiler feed. Based on the calculations performed, it can be seen that the company's DPMO value and sigma levels are 2,358.248 kg and 4.326. Based on the house of quality that has been arranged, it can be seen that the three technical responses (quality improvement strategies) with the highest ratings that can be prioritized by the company are counseling regarding the application of work instructions and SOPs to all employees, inspection of production machines or equipment before the production process is carried out, and implementation of safety stock and reorder points on fast-moving spare parts. Assuming that the quality improvement strategy is implemented, it can be seen that there was an increase in the Cp value to 1.297, an increase in the Cpk value to 0.7733, a decrease in the DPMO value to 1,257.65, and an increase in the sigma level to 4.521.